2017
DOI: 10.1155/2017/5798174
|View full text |Cite
|
Sign up to set email alerts
|

Setting Road Safety Targets in Cambodia: A Methodological Demonstration Using the Latent Risk Time Series Model

Abstract: We present the methodology used for estimating forecasts for the number of road traffic fatalities in 2011–2020 in Cambodia based on observed developments in Cambodian road traffic fatalities and motor vehicle ownership in the years 1995–2009. Using the latent risk time series model baseline forecasts for the fatality risk were estimated for the years 2010–2020. These baseline forecasts were then used to obtain estimates for the future number of fatalities based on three scenarios for the future Cambodian grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Therefore, an extrapolation is that the prerequisite to improve the effectiveness of the quantitative road safety management mode does not stop at how ambitious it should be, but more attention should be paid to other levels, including implementation, supervision, feasibility, and cost control. (3) An exception in contemporary studies is the research conducted in Cambodia in 2017 (12), which found that an ambitious target set was expected and forecasted to effectively Sign "+" refers to the positive association, which means that this study finds that higher target ambition or longer duration will bring better injury/fatality prevention outcomes. 2.…”
Section: Concluding Remarks and Policy Implicationsmentioning
confidence: 85%
See 3 more Smart Citations
“…Therefore, an extrapolation is that the prerequisite to improve the effectiveness of the quantitative road safety management mode does not stop at how ambitious it should be, but more attention should be paid to other levels, including implementation, supervision, feasibility, and cost control. (3) An exception in contemporary studies is the research conducted in Cambodia in 2017 (12), which found that an ambitious target set was expected and forecasted to effectively Sign "+" refers to the positive association, which means that this study finds that higher target ambition or longer duration will bring better injury/fatality prevention outcomes. 2.…”
Section: Concluding Remarks and Policy Implicationsmentioning
confidence: 85%
“…Such methods include cluster analysis and autoregression (31). Furthermore, regional studies referring to individual countries and areas have also been conducted, and regional uniqueness in terms of socio-economic development conditions has been considered [e.g., (12,14,15,22)].…”
Section: Quantitative Targets and Road Safety Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the Severity Index indicates the probability of dying once an accident has been occurred. Equations (1) to (3) show the expressions to obtain these indices [27]: These indexes can be employed to analyze and, in some cases, even to forecast the accidents rate and their consequences, as proposed by Commandeur et al [28].…”
Section: Road Safety Analysismentioning
confidence: 99%